(untitled) (International Seven Journal of Multidisciplinary, 2022)
An integrative review was conducted to examine biosafety protocols applied to paramedical micropigmentation for nipple areola complex reconstruction in women after mastectomy, literature was searched in SciELO PubMed LILACS Google Scholar and the CAPES Portal, with full text selection and standardized data extraction, the objective was to systematize updated norms and practice recommendations that ensure patient safety and care quality, findings indicate that services with adequate physical structure washable surfaces an exclusive handwashing sink and a unidirectional flow of clean and contaminated materials combined with written routines for hygiene antisepsis instrument processing and sterilization monitored by chemical and biological indicators show fewer local complications and more predictable esthetic outcomes, traceability of inputs through recording pigment lot numbers and expiration dates consistent use of personal protective equipment and preparation of a critical tray with barrier protections were identified as determinants of safety, psychosocial benefit was observed when consent education pre and post procedure guidance patient materials and scheduled follow ups were provided, frequent gaps included insufficient knowledge of sterilization parameters inappropriate reuse of disposables and limited training, it is concluded that excellence in paramedical micropigmentation depends on the convergence of qualified structure standardized and monitored processes technical competence and clinical governance supported by operational checklists and continuous improvement.